Upaya Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Pembelajaran Model Means-Ends Analysis (MEA) di SDN Sumbermulyo 01 Pati - Safa'atun Ni'mah (Lembaga Pendidikan Hikmatun Najah Blora, 2020)
The aim of this study are 1) To describe the learning process of the Means-Ends Analysis (MEA) model in learning Theme 2 Sub-theme 2 Learning 6, 2) To find out whether the Means-Ends Analysis (MEA) model can improve the learning activities of Class I students Semester I SDN Sumbermulyo 01 the academic year 2019/2020, 3) To find out whether the Means-Ends Analysis (MEA) model can improve student learning outcomes in Class V Semester I SDN Sumbermulyo 01 for the 2019/2020 academic year. This classroom action research used subjects and research settings for class V semester I of the 2019/2020 academic year SD Negeri Sumbermulyo 01, Winong District, Pati Regency. This classroom action research was carried out in 2 cycles of action in order to increase activity and learning outcomes Theme 2 Sub-theme 2 Learning 6. The results showed that in the first cycle the learning process obtained an average score of 2.60 in the sufficient category, the student learning activities in the first cycle obtained results. The average value is 69 in the sufficient category, and student learning outcomes in the first cycle showed that of the 30 students there were 22 students or 73% had completed the KKM while 8 students or 27% had not completed the KKM with an average score of 73. In cycle II the process learning and learning increased, namely the average score to 3.33 in the very good category, student learning activities increased to 89 in the good category, while the learning outcomes of students who had completed learning were 28 students or 93%, while those who had not finished learning were only 2 students or 7% with a mean score of 90. Tujuan dari penelitian ini yaitu: 1) Untuk mendeskripsikan proses pembelajaran model Means-Ends Analysis (MEA) pada pembelajaran Tema 2 Subtema 2 Pembelajaran 6, 2) Untuk mengetahui apakah melalui model Means-Ends Analysis (MEA) dapat meningkatkan aktivitas belajar siswa Kelas I Semester I SDN Sumbermulyo 01 tahun pelajaran 2019/2020, 3) Untuk mengetahui apakah melalui model Means-Ends Analysis (MEA) dapat meningkatkan hasil belajar siswa Kelas V Semester I SDN Sumbermulyo 01 tahun pelajaran 2019/2020.Penelitian tindakan kelas ini menggunakan subyek dan setting penelitian kelas V semester I Tahun Pelajaran 2019/2020 SD Negeri Sumbermulyo 01 Kecamatan Winong Kabupaten Pati. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus tindakan dalam rangka meningkatkanaktivitas dan hasil belajar Tema 2 Subtema 2 Pembelajaran 6.Hasil penelitian menunjukkan bahwa pada siklus I proses pembelajaran memperoleh nilai rata 2,60 dengan kategori cukup, aktivitas belajar siswa pada siklus I mendapatkan hasil nilai rata-rata yaitu 69 dengan kategori cukup, dan hasil belajar siswa pada siklus I menjunjukkan bahwa dari 30 siswa terdapat 22 siswa atau 73% tuntas KKM sedangkan 8 siswa atau 27% belum tuntas KKM dengan nilai rata-rata 73. Pada siklus II proses belajar pembelajaran meningkat yaitu nilaii rata-rata menjadi 3,33 dengan kategori sangat baik, aktivitas belajar siswa meningkat menjadi 89 dengan kategori baik, sedangkan hasil belajar siswa yang tuntas belajar sebanyak 28 siswa atau 93%, sedangkan yang belum tuntas belajar hanya 2 siswa atau 7% dengan nilai rata-rata 90.